Machine learning: the new language for applications - Venkatsai Siddesh Padala; Kathan Gandhi; D. V. Pushpalatha (IAES International Journal of Artificial Intelligence (IJ-AI), 2019)
Machine learning and artificial intelligence are becoming a significant influence on various research and commercial fields. This review attempts to equip the researchers and industrial practitioners with the knowledge of machine learning techniques and their applications in multiple fields. Challenges and future directions are also proposed, including data analysis suggestions, effective algorithms based on the situation, industrial implementation, organization’s risk tolerance, cost-benefit comparisons, and the future of machine learning techniques. Applications discussed in this paper range from technological development and health care to financial issues and sports analytics.